The role of brand commitment in the retail sector: The relation with open innovation - Jose Ribamar Siqueira; Nathalie Pe\~na-García; Enrique ter Horst; German Molina; Monica Villamil (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Firm-employee relationships are a prerequisite for customer-firm relationships and, consequently, to organizational success. The development of such relationships can be particularly challenging for retailers because of the complexity of the service component inherent to the environment in which they usually operate. For this reason, organizations need to align employee behaviors with the corporate brand promise so that they can perform a more active role as brand ambassadors. This issue becomes even more complex for organizations with a presence in foreign markets. This study focuses on how the adoption of in-role branding behavior by front-line employees (FLEs) can be influenced by the level of commitment FLEs display towards the corporate brand and how commitment is consequently influenced by corporate brand identity and corporate brand identity FLES' perception of their role within the organization. The object of the study was the employees of Falabella, a multinational retailer based in Chile with a strong presence in the Colombian market. Results obtained demonstrate that brand commitment positively and significantly impacts FLE brandoriented behavior in the retail context examined. More specifically, brand identity and role clarity positively impact brand commitment, leading to a positive impact on FLE brand behavior and job satisfaction. The results of this study offer valuable insight for scholars and practitioners regarding employee brand behavior's engendering process within a retail environment in an emerging market.
Keywords: 650; branding; front-line employees; retail; brand-commitment; role clarity; job satisfaction